Ulysses and His peregrini amores in the Latin Love Elegy - Danae Christidou
This article aims to trace the ‘unfaithful Ulysses’ motif in the Latin love elegy of the Augustan era. Roman elegists deconstruct Ulysses’s epic profile by turning his resourcefulness, his most celebrated virtue in epic poetry, into a vice; as a result, the elegiac Ulysses is a cunning sailor who charms women at every port he stops at, always being at the ready to sail away. This image of the epic hero is assessed in two conflicting ways: he is either judged for his insolent erotic behaviour, or he is applauded as the ideal ‘casual lover’, enviable to lovers who are unable to resist their self-destructing, obsessive passions.